Impact de la crise de la COVID-19 sur les familles francophones dans les Prairies canadiennes - Leis, Anne; De Moissac, Danielle; Proulx-Cullen, Elyse; Gnidehou, Sedami; Marchak, Kristan A.; Keough, Catelyn; Chaput, Mélanie; Turgeon, Marianne (Minorités linguistiques et société, 2025)
Contexte et but. Dans le contexte linguistique minoritaire où l’accès à des services en français est un défi, l’étude voulait documenter dans quelle mesure la crise de la pandémie avait eu un impact sur les familles francophones au Manitoba, Saskatchewan et Alberta. Méthodes. À partir des informations recueillies lors de 6 World Café du Monde, un sondage a été créé et distribué en ligne aux membres d’organismes francophones dans ces provinces. Des analyses descriptives et de régression ont été menées. Résultats. Des 319 familles, la grande majorité a reconnu l’impact négatif et anxiogène de la pandémie. Plusieurs facteurs de risque ont été identifiés : une compréhension moyenne ou faible de l’anglais, la déconnexion avec la communauté francophone locale, la difficulté de vivre en français en famille et de suivre la scolarité de ses enfants à la maison. Conclusion. La pandémie a été un défi pour les familles francophones des Prairies. Des ressources accrues en français et des politiques de soutien sont recommandées. , Background and aim. Within the linguistic minority context where access to services in French is a challenge, the study aimed to document to what extent the pandemic had an impact on Francophone families in Manitoba, Saskatchewan and Alberta. Methods. Based on the qualitative analysis of data collected in 6 World Cafés, an on-line survey was distributed to members of Francophone organizations in these provinces. Descriptive and regression analyses were conducted. Results. Of 319 families, the majority recognized the negative and anxiety provoking aspects of the pandemic. Several risk factors were identified: an average or below average mastery of English, isolation from the local Francophone community, difficulty with living in French with their family and supporting children’s education at home. Conclusion. The pandemic was a challenge for Francophone families in the Prairies. Additional resources in French and supportive policies are recommended.

Agir ensemble pour une Petite enfance en santé dans les communautés francophones et acadienne en situation minoritaire : Résultats et impacts du programme Petite enfance en santé 2024-2025 - Société Santé en français et les Réseaux de santé en français (2025)

Access to healthcare services and confidence in healthcare professionals’ management of malaria: the views of Francophone sub-Saharan African Immigrants living in western Canada - Vincent, Rémi; Coulibaly, Kongnon Sangué; Ahmed, Ali; Ahmed, Youssef; Hanna, Taylor A.; Ravi, Srilata; Hawkes, Michael T.; Gnidehou, Sedami (BMC Public Health, 2023)
Abstract Background There is a paucity of knowledge about the healthcare attitudes and practices of French-speaking immigrants originating from Sub-Saharan Africa (FISSA) living in minority settings. The purpose of this study was to characterize FISSA healthcare experiences and confidence in the malaria-related knowledge of health professionals in Edmonton. Methods A structured survey was used to examine a cohort of 382 FISSA (48% female; 52% male) living in Edmonton. FISSA general healthcare attitudes, experiences and satisfaction with the Canadian healthcare system were studied. Healthcare Competency Perception (HCP) was characterized by using an index score. Statistical analyses were performed to evaluate the impact of healthcare experiences and other outcomes. Results Intriguingly, while only 42% of FISSA had a French-speaking family physician, 83% (197/238) of those who had received health care services in Alberta found that access to medical treatment was easy, and 77% (188/243) were satisfied with received care. Although 70% (171/243) of FISSA did not receive services in French, 82% (199/243) surprisingly reported having good levels of comprehension during their visits. Satisfaction with care was associated with having a family physician (p = 0.018) and having health insurance (p= 0.041). Nevertheless, confidence in the healthcare system’s ability to treat malaria effectively was significantly lower, with only 39% (148/382) receiving a positive score on the HCP index. Conclusion This study provides an important insight into FISSA experience with and perception of the Alberta’s healthcare system.